A intertextualidade no romance O inverno e depois, de Luiz Antonio de Assis Brasil: literatura e musica - Brambila, Edemilson Antonio (2022)
This research focuses on the study of the intertextual presence between music and literature in the construction of the novel O Winter and Later, by the writer from Rio Grande do Sul, Luiz Antonio de Assis Brasil. Its main objective is to understand the intertextuality present in the narrative constructed by Luiz Antonio de Assis Brasil in O Winter and Later, paying attention to how it is influenced in its structuring aspect by the Concerto for Cello and Orchestra and in its narrative aspect by the work All Mornings of world. The corpora are composed of two literary works, the novel O Winter and Later (2016), by Luiz Antonio de Assis Brasil, and the novel All Mornings of the World (1993), by Pascal Quignard, and a musical work, the Concerto for Cello and Orchestra (1896), by Antonín Dvořák. The analyzes are anchored in studies about intertextuality, and the choice of this approach is justified by the fact that this theory focuses on the study of the productivity process of the literary text, built through the absorption or transformation of other texts. Thus, the theoretical-analytical basis of this work is supported, mainly, in the studies of Julia Kristeva (2005); Tiphaine Samoyault (2008); Tânia Franco Carvalhal (2006); Ingedore Grunfeld Villaça Koch (1991; 1997); Ingedore Grunfeld Villaça Koch, Anna Christina Bentes, Mônica Magalhães Cavalcante (2012); e Ingedore Grunfeld Villaça Koch, Vanda Maria Elias (2015). As for the methodological procedures, this corresponds to a comparative research, which also carries other characteristics regarding its typology, since it is an applied research regarding its nature, exploratory regarding its objectives, bibliographical and documentary regarding its procedures. technical, and qualitative as to their approach. As a result, it is possible to notice that the novel by Luiz Antonio de Assis Brasil is similar to the novel Todas as Manhãs do Mundo, by Pascal Quignard, through a thematic intertext, which has as its guiding line the main characters of the two narratives, their dilemmas, personal and professional issues. In the case of the relationship between O Inverno e Depois and the Concerto para Violoncelo e Orquestra, in addition to the thematic intertext, similar to the feature that makes up the intertext with Pascal Quignard, there is also a structural dialogue, which ends up bringing the two works closer together, as the Assisian novel is building in such a way as to mirror each of the movements of Antonín Dvořák's concert.